VIOLATION OF CONVERSATIONAL MAXIMS IN THE AVENGERS MOVIE - David Hamonangan Sihite and Sri Juriati Ownie (LINGUISTICA, 2015)
The study deals with the types of maxims violation in The Avengers movie’sscript. The objectives of the study were to discover the types of maxims violation,the most dominant maxim violation, and to explain the implication of the mostdominant maxim violation in The Avengers movie. The source of the data was theconversations in The Avengers movie. The data was the script of The Avengersmovie. There were 55 maxim violations in this research. The descriptivequalitative design was used to analyze the data. Descriptive qualitative research isa research method which describes the condition, events or situations. This studywas conducted by using descriptive qualitative method because the intention ofthis study was to describe how the maxims are violated. The results showed thatall types of maxim were violated; 39 utterances (70.90%) maxim violation ofrelation, 8 utterances (14.54%) maxim violation of quality, 5 utterances (9.09 %)maxim violation of quantity, 3 utterances (5.45%) maxim violation of manner.The most dominant type of maxim violation was the maxim violation of relation.The implication of maxim violation of relation as the dominant type of maxims inthe script of The Avengers movie was a strategy from the speakers to hidesomething, to hide the truth, and to create humor by giving irrelevant answer orchanging the topic.